Multiscale core-shell CoO@Co€PGN/CNTs composites aerogels for ultra-wide microwave absorption. (7th July 2022) - Xu, Dongwei; Ren, Yumei; Guo, Xiaoqin; Feng, Desheng; Yang, Run; Zhao, Biao; Zhang, Rui
Abstract: Multiscale and multicomponent design has been recognized as one of the most effective strategies to improve absorption performance of microwave absorption materials. Herein, the magnetic functional composites aerogels containing core-shell CoO@Co nanoparticles, porous graphene nanosheets (PGN) and carbon nanotubes (CNTs) were successfully fabricated by combining solvothermal method and subsequently calcination processes. The results demonstrated that the calcination temperatures determined the chemical composition (CoO, α-Co, β-Co and CNTs) and complex structure (core-shell and porous characteristics) of the resultant composites aerogels, which affected the magnetic properties and electromagnetic parameters. Interestingly, at the calcination temperature of 650 °C, CNTs were uniformly grown on the surface of porous graphene nanosheets under self-generated cobalt metal catalyst. As expected, the paraffin-based composites aerogels of S650 samples with 15 wt% filling contents presented outstanding microwave absorption performance (MAP) in view of both minimum reflection loss ( RLmin, −63.39 dB, d = 3.4 mm) and the effective absorption bandwidth ( EAB, RL values below −10 dB, 6.5 GHz, d = 2.4 mm). Considering these excellent properties in mind, the composites aerogels with unique complex structures hold great promise as synergistic microwave absorbers for electromagnetic pollution. Graphical abstract: Image 1